Penerapan Adaptasi Kebiasaan Baru Dalam Meningkatkan Kesehatan Siswa-Siswi - Nourmayansa Vidya Anggraini; Diah Ratnawati (STKIP Andi Matappa, 2021)
SMA X Kec. Baros has a vision and mission to make his students excel and have noble character. SMA X students need to be equipped with non-academic knowledge to increase their understanding of the adaptation of new habits, especially provision through health education activities. This health education program is a community service using a quantitative approach to measure the level of understanding of students regarding the adaptation of new habits. Students level of understanding was measured using a quasi experimental method. Comparison of the level of effectiveness of the implementation of health education programs between before and after was measured by group pre-test and post-test. Paired sample test was used to analyze the data. The test results showed a significant difference between the pre-test and post-test scores of students knowledge about the adaptation of new habits with a p value <0.001. Based on these results, it can be concluded that health education is effective in increasing the knowledge of SMA X Kec. Baros.